SPREAD BASED MENINGKATKAN LABA PERUSAHAAN PERBANKAN DI INDONESIA - Sari, Laynita; Ananda, Febryandhie; Zulfia, Dewi; Rivandi, Muhammad; Dewi, Mike Kusuma (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of spread based on the profit of banking companies in Indonesia. Spread Based and company profits are obtained from the company's financial statements and from the Indonesia Stock Exchange website. The research sample amounted to forty-five banking companies in Indonesia from 2017-2022, which were determined by the purposive sampling method. The type of data used is secondary data in the form of annual reports of banking companies for the 2017-2022 period. The data analysis technique uses multiple linear regression analysis with the help of the E-Views program version 12. This study found that spread-based provides empirical evidence of a significant positive effect on the profits of banking companies listed on the Indonesia Stock Exchange in 2017-2022